Breaking sarcomeres by in vitro exercise - Orfanos, Zacharias (Sci Rep, 2016)
Eccentric exercise leads to focal disruptions in the myofibrils, referred to as “lesions”. These structures are thought to contribute to the post-exercise muscle weakness, and to represent areas of mechanical damage and/or remodelling. Lesions have been investigated in human biopsies and animal samples after exercise. However, this approach does not examine the mechanisms behind lesion formation, or their behaviour during contraction. To circumvent this, we used electrical pulse stimulation (EPS) to simulate exercise in C2C12 myotubes, combined with live microscopy. EPS application led to the formation of sarcomeric lesions in the myotubes, resembling those seen in exercised mice, increasing in number with the time of application or stimulation intensity. Furthermore, transfection with an EGFP-tagged version of the lesion and Z-disc marker filamin-C allowed us to observe the formation of lesions using live cell imaging. Finally, using the same technique we studied the behaviour of these structures during contraction, and observed them to be passively stretching. This passive behaviour supports the hypothesis that lesions contribute to the post-exercise muscle weakness, protecting against further damage. We conclude that EPS can be reliably used as a model for the induction and study of sarcomeric lesions in myotubes in vitro.